PEMBELAJARAN DEMOKRATIS MENUJU PROFESIONALISME GURU - I Nengah Sudja (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2013)
Learning is the process of changing behavior as an impact obtained by the five senses that is relatively permanent. In the teaching-learning process, the teachers need a situation and condition that are supportive and condusive. At the past, the students were afraid of their teachers. They were like in a jail. Meanwhile, in the present, the teachers need to understand the surrounding and the student’s chracteristics. Regarding on that notion, the teachers are expected to implement and stimulate the students with several methods of innovative teaching.